ANTERIOR OPEN-BITE TREATMENT BY MEANS OF ZYGOMATIC MINIPLATES: A CASE REPORT - BEYCAN, KADİR (ISTANBUL UNIV, FAC DENTISTRY, 2016)
This case report presents the treatment of a patient with skeletal Cl II malocclusion and anterior open-bite who was treated with zygomatic miniplates through the intrusion of maxillary posterior teeth. A 16-year-old female patient with a chief complaint of anterior open-bite had a symmetric face, incompetent lips, convex profile, retrusive lower lip and chin. Intraoral examination showed that the buccal segments were in Class II relationship, and there was anterior open-bite (overbite -6.5 mm). The cephalometric analysis showed Class II skeletal relationship with increased lower facial height. The treatment plan included intrusion of the maxillary posterior teeth using zygomatic miniplates followed by fixed orthodontic treatment. At the end of treatment Class I canine and molar relationships were achieved, anterior open-bite was corrected and normal smile line was obtained. Skeletal anchorage using zygomatic miniplates is an effective method for open-bite treatment through the intrusion of maxillary posterior teeth.
Keywords: Class II malocclusion; anterior open-bite; zygomatic miniplate; skeletal anchorage; smile line; SKELETAL ANCHORAGE; MOLAR INTRUSION; IMPLANTS; SYSTEM